The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1145/3544977
|View full text |Cite
|
Sign up to set email alerts
|

GRACE: A General Graph Convolution Framework for Attributed Graph Clustering

Abstract: Attributed graph clustering (AGC) is an important problem in graph mining as more and more complex data in real-world have been represented in graphs with attributed nodes. While it is a common practice to leverage both attribute and structure information for improved clustering performance, most existing AGC algorithms consider only a specific type of relations, which hinders their applicability to integrate various complex relations into node attributes for AGC. In this paper, we propose GRACE, an extended g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Graph convolution [38] embeds node features and topological information into a lowdimensional space by convolutional encoding of the adjacency matrix A and the feature matrix X:…”
Section: Graph Convolutionmentioning
confidence: 99%
“…Graph convolution [38] embeds node features and topological information into a lowdimensional space by convolutional encoding of the adjacency matrix A and the feature matrix X:…”
Section: Graph Convolutionmentioning
confidence: 99%
“…As more and more complicated data from the real world are represented in graphs with attributed nodes, attributed grap h clustering (AGC) has become a significant issue in graph mining. Kamhoua et al [45] suggested an expanded general graph convolution framework for attributed graph clustering (GRACE), often known as an AGC tasks. Zhang et al [21] suggested a community affiliation graph model that can capture overlapping, non-overlapping, and hierarchical layered overlapping communities successfully.…”
Section: Related Workmentioning
confidence: 99%